Effects of supplementing different chromium histidinate complexes on glucose and lipid metabolism and related protein expressions in rats fed a high-fat diet - Şahin, Kazım; Küçük, Ömersman; Orhan, Cemal; Erten, Fusun; Şahin, Nurhan; Komorowski, James R. (Elsevier Gmbh, 2021)
Background: The objective of this study was to investigate the effects of different chromium histidinate (CrHis) complexes added to the diet of rats fed a high-fat diet (HFD) on body weight changes, glucose and lipid metabolism parameters, and changes in biomarkers such as PPAR-?, IRS-1, GLUTs, and NF-?B proteins. Methods: Forty-two Sprague?Dawley rats were divided equally into six groups and fed either a control, an HFD, or an HFD supplemented with either CrHis1, CrHis2, CrHis3, or a combination of the CrHis complexes as CrHisM. Results: Feeding an HFD to rats increased body weights, HOMA-IR values, fasting serum glucose, insulin, leptin, free fatty acid, total cholesterol, low-density lipoprotein cholesterol, and MDA concentrations as well as AST activities, and decreased serum and brain serotonin concentrations compared with rats fed a control diet (P < 0.0001). The levels of the PPAR-?, IRS-1, and GLUTs in the liver and brain decreased, while NF-?B level increased, with feeding an HFD (P < 0.05). Although all the CrHis supplements reversed the negative effects of feeding an HFD (P < 0.05), the CrHis1 complex was most effective in changing the protein levels, while CrHisM was most effective in influencing certain parameters such as body weight and serum metabolites. Conclusion: The results of the present work suggest that the CrHis1 complex is most potent for alleviating the negative effects of feeding an HFD. The efficacy of CrHisM is likely due to the presence of the CrHis1 complex.
Keywords: Chromium histidinate; High-fat diet; Insulin; Lipids; Biomarkers; Rats